A method for preparing waterless taphole mud for preventing leakage

By using a combination of modified carbon black and other raw materials in the water-free cannon mud, the problems of loosening and increased porosity caused by moisture during the preparation process of water-free cannon mud are solved, and the porosity and pressure resistance are achieved. The effect of strength prevents leakage and improves the stability and safety of the working state of the iron mouth.

CN119219400BActive Publication Date: 2025-02-25LUOYANG SHENG TIE REFRACTORY MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411755180.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-25
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The existing water-free cannon mud contains moisture during the preparation process, which leads to loosening of the cannon mud tissue and increased porosity, reduces corrosion resistance and high-temperature and compressive strength, increases the probability of leakage breakage and pore size expansion, and affects the stability of the iron discharge process. Sex and safety.

Method used

By preparing modified carbon black and combining it with other raw materials such as corundum, bauxite, clay, silicon carbide and calcium carbonate, etc., drying and stirring, the porosity rate is reduced, and the density of the cannon mud is increased. Pressure resistance to prevent leakage.

Benefits of technology

It effectively reduces the porosity of the waterless cannon mud, improves its pressure resistance, prevents leakage, and improves the stability and safety of the working state of the iron mouth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219400B_ABST
    Figure CN119219400B_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing anhydrous taphole mud for preventing leakage, and belongs to the technical field of refractory materials. The preparation method comprises the following steps: S1, by weight, 28-32 parts of corundum, 25-30 parts of bauxite, 9-13 parts of clay, 5-8 parts of kyanite, 7-12 parts of ferrosilicon nitride, 12-17 parts of silicon carbide, 5-8 parts of calcium carbonate and 7-10 parts of modified carbon black are put into a dryer, heated to 100-120°C, stirred and dehydrated at 0.5-0.7MPa, and when the Engler viscosity is 9-11 and the water content is less than 0.5wt%, a dry raw material is obtained; S2, the dry raw material is put into a mixer, stirred and mixed, and a first mixture is obtained; S3, 10-15 parts of a binder is added to the first mixture, and stirred and mixed, and a second mixture is obtained; S4, the second mixture is extruded from a discharge port of the mixer, and the anhydrous taphole mud for preventing leakage is obtained. The present invention can reduce the apparent porosity, improve the compressive strength of the anhydrous taphole mud, and thus effectively prevent the occurrence of leakage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a method for preparing waterless taphole mud for preventing leakage. Background Art

[0002] Anhydrous taphole clay refers to taphole clay made from tar, resin, etc. as binders, and corundum, bauxite, clay, silicon carbide, coke powder, etc. as raw materials. It is used to block the taphole of a blast furnace to ensure that molten iron and slag can be discharged smoothly during the tapping process, while maintaining the stability of the taphole aperture to ensure uniform tapping.

[0003] During the preparation of existing waterless cannon clay, the raw materials generally contain water. During the heating process of the cannon clay, the evaporation of water in the raw materials will cause the cannon clay structure to become loose and the apparent porosity to increase. At the same time, the binder and other raw materials will also affect the apparent porosity of the cannon clay. The increase in apparent porosity reduces the corrosion resistance and high-temperature compressive strength of the cannon clay, resulting in an increased probability of leakage at the iron mouth. At the same time, it expands the iron mouth aperture, shortens the iron tapping time, and easily causes a large amount of slag iron to gush out during the iron tapping process, affecting production and endangering safety. Summary of the invention

[0004] In order to solve the problems existing in the background technology, the present invention provides a method for preparing waterless taphole clay that prevents leakage, which can reduce the apparent porosity and improve the compressive strength of the waterless taphole clay, thereby effectively preventing the occurrence of leakage and improving the stability and safety of the iron mouth working state.

[0005] In order to achieve the above object, the present invention provides a method for preparing waterless taphole mud to prevent leakage, comprising the following steps:

[0006] S1. Put 28-32 parts of corundum, 25-30 parts of bauxite, 9-13 parts of clay, 5-8 parts of kyanite, 7-12 parts of ferrosilicon nitride, 12-17 parts of silicon carbide, 5-8 parts of calcium carbonate and 7-10 parts of modified carbon black into a dryer by weight, heat to 100-120° C., stir and dehydrate at 0.5-0.7 MPa, and obtain a dry raw material when the Engler viscosity is 9-11 and the water content is less than 0.5wt%;

[0007] S2, putting the dry raw material obtained in S1 into a mixer for stirring and mixing to obtain a first mixed material;

[0008] S3, adding 10-15 parts of a binder to the first mixture obtained in S2, and continuing to stir and mix to obtain a second mixture;

[0009] S4, the second mixed material obtained in S3 is squeezed out from the discharge port of the mixer to obtain leak-proof waterless taphole mud.

[0010] Furthermore, the preparation method of the modified carbon black comprises the following steps:

[0011] A1. Add 100 g of carbon black and 800-1000 mL of nitric acid solution into a beaker, react at 45-50 ° C for 3-3.5 hours, then cool to room temperature, filter, and obtain treated carbon black;

[0012] A2, washing the treated carbon black obtained in A1 with deionized water until the pH value of the washing liquid is constant, thereby obtaining washed carbon black;

[0013] A3. Dry the cleaned carbon black obtained in A2 to obtain modified carbon black.

[0014] Furthermore, in the A1, the mass fraction of the nitric acid solution is 62-68%.

[0015] Furthermore, in A3, the drying temperature is 120-130° C., and the drying time is 5-6 hours.

[0016] Furthermore, in the S1, the particle size of corundum is 0.27-0.35 mm, the particle size of bauxite is 1-3 mm, the particle size of clay is 0.074-0.085 mm, the particle size of kyanite is 0.24-0.35 mm, the particle size of ferrosilicon nitride is 0.084-0.095 mm, the particle size of silicon carbide is 0.071-0.083 mm, and the particle size of calcium carbonate is 0.84-0.95 mm.

[0017] Furthermore, in S2, at 42-46°C, the rotation speed of the stirrer is 600-650 r / min, and the stirring time is 2-4 min.

[0018] Furthermore, in S3, at 42-46° C., the rotation speed of the stirrer is 800-850 r / min, and the stirring time is 20-24 min.

[0019] Furthermore, in S4, the material temperature during extrusion is controlled to be 45-50°C.

[0020] Furthermore, the binder is tar.

[0021] This application has the following beneficial effects:

[0022] During the use of the anhydrous cannon mud of the present invention, calcium carbonate will decompose at high temperature to generate calcium oxide and carbon dioxide. On the one hand, the modified carbon black, because it is a fine particle material, can be filled in the pores generated by the decomposition of calcium carbonate, which helps to reduce the apparent porosity and increase the density of the material; on the other hand, the modified carbon black can also capture the carbon dioxide generated by the decomposition of calcium carbonate by physical adsorption and chemical adsorption, reduce the escape of carbon dioxide, and thus reduce the apparent porosity; and, the modified carbon black can improve the thermal conductivity of the cannon mud, making the sintering (heating) process more uniform, thereby promoting the above two effects and accelerating the sintering and densification process of the cannon mud.

[0023] Due to the synergistic effect of modified carbon black and calcium carbonate, the network structure formed by the cannon clay during the sintering process is tighter, which reduces the gas escape channel and the apparent porosity, and jointly promotes the densification and structural stability of the cannon clay.

[0024] 2. In the preparation of the modified carbon black of the present invention, it is obtained by surface oxidation treatment of carbon black, maintaining its filling capacity and capture capacity, that is, maintaining its synergistic ability with calcium carbonate while enhancing its surface activity, making it easier to chemically react with other components in the cannon mud or form stable chemical bonds, thereby further improving the overall structural density, strength and stability of the cannon mud. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 , a comparative trend chart of the apparent porosity and compressive strength test data of the anhydrous cannon muds prepared in Examples 1 to 6 of the present invention and Comparative Examples 1 to 5. DETAILED DESCRIPTION

[0026] The present application is further described in detail below with reference to the embodiments.

[0027] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0028] Example 1: (1) Preparing modified carbon black, the preparation method thereof comprises the following steps:

[0029] A1. Add 100g carbon black and 900mL nitric acid solution into a beaker and react at 47°C for 3.2h. The temperature and time are chosen to ensure that the nitric acid can fully react with the carbon black and introduce oxygen-containing functional groups, thereby improving the surface activity of the carbon black. Then cool to room temperature and filter to remove unreacted nitric acid and other soluble impurities to obtain treated carbon black.

[0030] Among them, the mass fraction of nitric acid solution is 65%.

[0031] The carbon black is superconducting (thermal and electrical conductive) carbon black (M90), with a heating loss of ≤1.0% and a specific surface area of ​​450±10m 2 / g, purchased from Hebei Moyu Chemical Co., Ltd.

[0032] A2. Wash the treated carbon black obtained in A1 with deionized water until the pH value of the washing liquid is constant to further remove residual acidic substances and other impurities to obtain washed carbon black.

[0033] A3. Dry the cleaned carbon black obtained in A2 at a temperature of 125° C. for 5.5 h to remove moisture from the carbon black and obtain dry modified carbon black.

[0034] (2) Preparing waterless taphole mud to prevent leakage, the preparation method comprises the following steps:

[0035] S1. By weight, 30 parts of corundum, 28 parts of bauxite, 11 parts of clay, 6 parts of kyanite, 9 parts of ferrosilicon nitride, 14 parts of silicon carbide, 6 parts of calcium carbonate and 9 parts of modified carbon black are put into a dryer, heated to 110°C, stirred and dehydrated at 0.6MPa. The high-pressure environment helps to accelerate the evaporation of water. At the same time, the components are evenly distributed and mixed by stirring to avoid local overheating or unevenness of the mixture.

[0036] When the Engler viscosity of the mixture reaches 9-11 and the water content is less than 0.5wt%, the heating and stirring are stopped to obtain a dry raw material. The Engler viscosity is an important indicator for measuring the fluidity of the mixture. Appropriate viscosity can ensure that the material has good fluidity and filling properties during the molding process.

[0037] Among them, the particle sizes of each raw material are roughly measured as follows: the particle size of corundum is 0.27-0.35mm, the particle size of bauxite is 1-3mm, the particle size of clay is 0.074-0.085mm, the particle size of kyanite is 0.24-0.35mm, the particle size of ferrosilicon nitride is 0.084-0.095mm, the particle size of silicon carbide is 0.071-0.083mm, and the particle size of calcium carbonate is 0.84-0.95mm.

[0038] The sources of raw materials are as follows: Corundum is purchased from Henan Youji Environmental Protection Technology Co., Ltd. Bauxite is purchased from Lingshou County Quanfeng Mineral Products Processing Plant Clay is purchased from Gongyi Xuchen Refractory Co., Ltd., model 01, specification 325 mesh Kyanite is purchased from Lingshou County Pengxia Furnace Lining Material Processing Plant Ferrosilicon Nitride is purchased from Anyang Dingxing Metallurgical Refractory Co., Ltd. Silicon carbide is purchased from Henan Dongli New Materials Co., Ltd. Calcium carbonate is purchased from Hunan Xiangyi Calcium Industry Co., Ltd.

[0039] S2. The dried raw material obtained in S1 is put into a mixer and stirred at 45° C., with a rotation speed of 620 r / min and a stirring time of 3 min to obtain a first mixed material.

[0040] S3. According to the same standard weight parts, 12 parts of binder are added to the first mixture obtained in S2, and stirring is continued. Specifically, at 45°C, the speed of the stirrer is 820r / min, and the stirring time is 22min to mix well to obtain a second mixture.

[0041] Among them, the binder is tar, which is purchased from Dongguan County Jinda Chemical Co., Ltd.

[0042] S4. The second mixed material obtained in S3 is extruded from the discharge port of the mixer, and the material temperature during extrusion is controlled to be 48°C (slightly higher than the heating temperature during stirring in S3), so as to obtain leak-proof waterless taphole mud.

[0043] Example 2: The difference between this example and Example 1 is that: (1) preparing modified carbon black, the preparation method thereof comprises the following steps:

[0044] A1. Add 100 g of carbon black and 800 mL of nitric acid solution into a beaker, react at 45 °C for 3 h, then cool to room temperature and filter to obtain treated carbon black.

[0045] Among them, the mass fraction of nitric acid solution is 62%.

[0046] The carbon black is superconducting (thermal and electrical conductive) carbon black (M90), with a heating loss of ≤1.0% and a specific surface area of ​​450±10m 2 / g, purchased from Hebei Moyu Chemical Co., Ltd.

[0047] A2. Wash the treated carbon black obtained in A1 with deionized water until the pH value of the washing liquid is constant to obtain washed carbon black.

[0048] A3. Dry the cleaned carbon black obtained in A2 at a temperature of 120°C for 5 hours to obtain modified carbon black.

[0049] Example 3: The difference between this example and Example 1 is that: (1) preparing modified carbon black, the preparation method thereof comprises the following steps:

[0050] A1. Add 100 g of carbon black and 1000 mL of nitric acid solution into a beaker, react at 50 °C for 3.5 h, then cool to room temperature and filter to obtain treated carbon black.

[0051] Among them, the mass fraction of nitric acid solution is 68%.

[0052] The carbon black is superconducting (thermal and electrical conductive) carbon black (M90), with a heating loss of ≤1.0% and a specific surface area of ​​450±10m 2 / g, purchased from Hebei Moyu Chemical Co., Ltd.

[0053] A2. Wash the treated carbon black obtained in A1 with deionized water until the pH value of the washing liquid is constant to obtain washed carbon black.

[0054] A3. Dry the cleaned carbon black obtained in A2 at a temperature of 130°C for 6 hours to obtain modified carbon black.

[0055] Embodiment 4: The difference between this embodiment and embodiment 1 is that: (2) preparing anti-leakage waterless taphole mud, the preparation method thereof comprises the following steps:

[0056] S1. Put 28 parts of corundum, 25 parts of bauxite, 9 parts of clay, 5 parts of kyanite, 7 parts of ferrosilicon nitride, 12 parts of silicon carbide, 5 parts of calcium carbonate and 7 parts of modified carbon black into a dryer by weight, heat to 100°C, stir and dehydrate at 0.5MPa, and stop heating and stirring when the Engler viscosity of the mixture reaches 9-11 and the water content is less than 0.5wt% to obtain a dry raw material.

[0057] S2. The dried raw material obtained in S1 is put into a mixer and stirred at 42° C., with a rotation speed of 600 r / min and a stirring time of 2 min to obtain a first mixed material.

[0058] S3. Add 10 parts of binder tar to the first mixture obtained in S2, and continue stirring. Specifically, at 42° C., the speed of the stirrer is 800 r / min, and the stirring time is 20 min to mix well to obtain a second mixture.

[0059] S4. The second mixed material obtained in S3 is extruded from the discharge port of the mixer, and the material temperature during extrusion is controlled to be 45° C., thereby obtaining leak-proof waterless taphole mud.

[0060] Example 5: The difference between this example and Example 1 is that: (2) the water-free taphole mud for preventing leakage is prepared, and the preparation method thereof comprises the following steps:

[0061] S1. Put 32 parts of corundum, 30 parts of bauxite, 13 parts of clay, 8 parts of kyanite, 12 parts of ferrosilicon nitride, 17 parts of silicon carbide, 8 parts of calcium carbonate and 10 parts of modified carbon black into a dryer by weight, heat to 120°C, stir and dehydrate at 0.7MPa, and stop heating and stirring when the Engler viscosity of the mixture reaches 9-11 and the water content is less than 0.5wt% to obtain a dry raw material.

[0062] S2. The dried raw material obtained in S1 is put into a mixer and stirred at 46° C., with a rotation speed of 650 r / min and a stirring time of 4 min to obtain a first mixed material.

[0063] S3. Add 15 parts of binder tar to the first mixture obtained in S2, and continue stirring. Specifically, at 46° C., the speed of the stirrer is 850 r / min, and the stirring time is 24 min to mix well to obtain a second mixture.

[0064] S4, extruding the second mixed material obtained in S3 from the discharge port of the mixer, controlling the material temperature during extrusion to be 50°C, and obtaining anti-leakage waterless taphole mud.

[0065] Example 6: The difference between this example and Example 1 is that: (2) the water-free taphole mud for preventing leakage is prepared, and the preparation method thereof comprises the following steps:

[0066] S1. By weight, 31 parts of corundum, 26 parts of bauxite, 12 parts of clay, 7 parts of kyanite, 8 parts of ferrosilicon nitride, 15 parts of silicon carbide, 7 parts of calcium carbonate and 9 parts of modified carbon black are put into a dryer, heated to 110°C, stirred and dehydrated at 0.6MPa, and when the Engler viscosity of the mixture reaches 9-11 and the water content is less than 0.5wt%, the heating and stirring are stopped to obtain a dry raw material.

[0067] S2. The dried raw material obtained in S1 is put into a mixer and stirred at 44° C., with a rotation speed of 630 r / min and a stirring time of 3 min to obtain a first mixed material.

[0068] S3. Add 14 parts of binder tar to the first mixture obtained in S2, and continue stirring. Specifically, at 45° C., the speed of the stirrer is 830 r / min, and the stirring time is 22 min to mix well to obtain a second mixture.

[0069] S4. The second mixed material obtained in S3 is extruded from the discharge port of the mixer, and the material temperature during extrusion is controlled to be 48° C., thereby obtaining leak-proof waterless taphole mud.

[0070] Comparative Example 1: The difference between this comparative example and Example 1 is that in the preparation of anti-leakage anhydrous taphole mud, modified carbon black is replaced by carbon black.

[0071] Specifically, (2) preparing anti-leakage waterless taphole mud, the preparation method thereof comprises the following steps:

[0072] S1. By weight, 30 parts of corundum, 28 parts of bauxite, 11 parts of clay, 6 parts of kyanite, 9 parts of ferrosilicon nitride, 14 parts of silicon carbide, 6 parts of calcium carbonate and 9 parts of carbon black are put into a dryer, heated to 110° C., stirred and dehydrated at 0.6 MPa, and when the Engler viscosity of the mixture reaches 9-11 and the water content is less than 0.5wt%, the heating and stirring are stopped to obtain a dry raw material.

[0073] S2. The dried raw material obtained in S1 is put into a mixer and stirred at 45° C., with a rotation speed of 620 r / min and a stirring time of 3 min to obtain a first mixed material.

[0074] S3. According to the same standard weight proportion, 12 parts of binder tar are added to the first mixture obtained in S2, and stirring is continued. Specifically, at 45°C, the speed of the stirrer is 820r / min, and the stirring time is 22min to mix well to obtain a second mixture.

[0075] S4, extruding the second mixed material obtained in S3 from the discharge port of the mixer, controlling the material temperature during extrusion to be about 48°C, and obtaining anti-leakage waterless taphole mud.

[0076] Comparative Example 2: The difference between this comparative example and Example 1 is that in the preparation of the anti-leakage anhydrous cannon mud, calcium carbonate is deleted and the modified carbon black is replaced by carbon black.

[0077] Specifically, (2) preparing anti-leakage waterless taphole mud, the preparation method thereof comprises the following steps:

[0078] S1. By weight, 30 parts of corundum, 28 parts of bauxite, 11 parts of clay, 6 parts of kyanite, 9 parts of ferrosilicon nitride, 14 parts of silicon carbide and 9 parts of carbon black are put into a dryer, heated to 110° C., stirred and dehydrated at 0.6 MPa, and when the Engler viscosity of the mixture reaches 9-11 and the water content is less than 0.5wt%, the heating and stirring are stopped to obtain a dry raw material.

[0079] S2. The dried raw material obtained in S1 is put into a mixer and stirred at 45° C., with a rotation speed of 620 r / min and a stirring time of 3 min to obtain a first mixed material.

[0080] S3. According to the same standard weight proportion, 12 parts of binder tar are added to the first mixture obtained in S2, and stirring is continued. Specifically, at 45°C, the speed of the stirrer is 820r / min, and the stirring time is 22min to mix well to obtain a second mixture.

[0081] S4, extruding the second mixed material obtained in S3 from the discharge port of the mixer, controlling the material temperature during extrusion to be about 48°C, and obtaining anti-leakage waterless taphole mud.

[0082] Comparative Example 3: The difference between this comparative example and Example 1 is that calcium carbonate is deleted in the preparation of the anti-leakage anhydrous cannon mud.

[0083] Specifically, (2) preparing anti-leakage waterless taphole mud, the preparation method thereof comprises the following steps:

[0084] S1. By weight, 30 parts of corundum, 28 parts of bauxite, 11 parts of clay, 6 parts of kyanite, 9 parts of ferrosilicon nitride, 14 parts of silicon carbide and 9 parts of modified carbon black are put into a dryer, heated to 110°C, stirred and dehydrated at 0.6MPa, and when the Engler viscosity of the mixture reaches 9-11 and the water content is less than 0.5wt%, the heating and stirring are stopped to obtain a dry raw material.

[0085] S2. The dried raw material obtained in S1 is put into a mixer and stirred at 45° C., with a rotation speed of 620 r / min and a stirring time of 3 min to obtain a first mixed material.

[0086] S3. According to the same standard weight proportion, 12 parts of binder tar are added to the first mixture obtained in S2, and stirring is continued. Specifically, at 45°C, the speed of the stirrer is 820r / min, and the stirring time is 22min to mix well to obtain a second mixture.

[0087] S4, extruding the second mixed material obtained in S3 from the discharge port of the mixer, controlling the material temperature during extrusion to be about 48°C, and obtaining anti-leakage waterless taphole mud.

[0088] Comparative Example 4: The difference between this comparative example and Example 1 is that modified carbon black is deleted in the preparation of anti-leakage anhydrous taphole mud.

[0089] Specifically, (2) preparing anti-leakage waterless taphole mud, the preparation method thereof comprises the following steps:

[0090] S1. By weight, 30 parts of corundum, 28 parts of bauxite, 11 parts of clay, 6 parts of kyanite, 9 parts of ferrosilicon nitride, 14 parts of silicon carbide and 6 parts of calcium carbonate are put into a dryer, heated to 110°C, stirred and dehydrated at 0.6MPa, and when the Engler viscosity of the mixture reaches 9-11 and the water content is less than 0.5wt%, the heating and stirring are stopped to obtain a dry raw material.

[0091] S2. The dried raw material obtained in S1 is put into a mixer and stirred at 45° C., with a rotation speed of 620 r / min and a stirring time of 3 min to obtain a first mixed material.

[0092] S3. According to the same standard weight proportion, 12 parts of binder tar are added to the first mixture obtained in S2, and stirring is continued. Specifically, at 45°C, the speed of the stirrer is 820r / min, and the stirring time is 22min to mix well to obtain a second mixture.

[0093] S4, extruding the second mixed material obtained in S3 from the discharge port of the mixer, controlling the material temperature during extrusion to be about 48°C, and obtaining anti-leakage waterless taphole mud.

[0094] Comparative Example 5: The difference between this comparative example and Example 1 is that calcium carbonate and modified carbon black are deleted in the preparation of anti-leakage anhydrous taphole mud.

[0095] Specifically, (2) preparing anti-leakage waterless taphole mud, the preparation method thereof comprises the following steps:

[0096] S1. By weight, 30 parts of corundum, 28 parts of bauxite, 11 parts of clay, 6 parts of kyanite, 9 parts of ferrosilicon nitride and 14 parts of silicon carbide are put into a dryer, heated to 110° C., stirred and dehydrated at 0.6 MPa, and when the Engler viscosity of the mixture reaches 9-11 and the water content is less than 0.5wt%, the heating and stirring are stopped to obtain a dry raw material.

[0097] S2. The dried raw material obtained in S1 is put into a mixer and stirred at 45° C., with a rotation speed of 620 r / min and a stirring time of 3 min to obtain a first mixed material.

[0098] S3. According to the same standard weight proportion, 12 parts of binder tar are added to the first mixture obtained in S2, and stirring is continued. Specifically, at 45°C, the speed of the stirrer is 820r / min, and the stirring time is 22min to mix well to obtain a second mixture.

[0099] S4, extruding the second mixed material obtained in S3 from the discharge port of the mixer, controlling the material temperature during extrusion to be about 48°C, and obtaining anti-leakage waterless taphole mud.

[0100] Test example: Test object: Anhydrous taphole mud was prepared by Example 1-Example 6 and Comparative Example 1-Comparative Example 5.

[0101] Test items and method basis: 1. Apparent porosity: Bake the anhydrous taphole mud (test object) to about 80℃, then divide it into small pieces the size of fingers, fill it into a triple mold of 40mm*40mm*160mm, pay attention to the four corners, and then knock it with a wooden hammer to make it tightly filled; after the strip sample is cooled and hardened, take out the strip sample, put it into an iron box (the size of the iron box is slightly larger than the size of the strip sample), put it into an oven for insulation at 450℃ for 5h; sinter the heat-treated strip sample in an electric furnace and keep it at 1350℃ for 3h; finally, test the apparent porosity in accordance with GB / T 2997-2000.

[0102] 2. Compressive strength: refer to the determination method in YB / T 5115-2014. The size of the sample (test object) is 114mm*114mm*65mm, and the measurement conditions are 1350℃*3h.

[0103] Test results: See Table 1.

[0104]

[0105] Result analysis: Analyze Example 1-Example 6 and combine the data in Table 1 and Figure 1 It can be seen that the apparent porosity test data of the anhydrous cannon clay prepared by the present invention is as low as below 25.2%, and the compressive strength is as high as above 30.9 MPa, indicating that the anhydrous cannon clay prepared by the present invention has low apparent porosity and high compressive strength, can effectively prevent the occurrence of leakage, and improve the stability and safety of the iron mouth working state.

[0106] Analyze Example 1 and Comparative Examples 1-5 and combine the data in Table 1 and Figure 1 By comparing Comparative Example 4 with Comparative Example 5, it can be seen that compared with Comparative Example 5, more calcium carbonate is added to the raw material components of Comparative Example 4. As a result, the test data of the apparent porosity of the anhydrous cannon mud obtained in Comparative Example 4 is 32.1%, which is greater than 29.8% of Comparative Example 5; and the test data of the compressive strength of the anhydrous cannon mud obtained in Comparative Example 4 is 25.2MPa, which is less than 27.3MPa of Comparative Example 5. It shows that adding calcium carbonate alone to the raw material components will increase the apparent porosity of the anhydrous cannon mud and reduce the compressive strength.

[0107] By comparing Comparative Example 2 with Comparative Example 5, it can be seen that compared with Comparative Example 5, more carbon black is added to the raw material components of Comparative Example 2. As a result, the apparent porosity test data of the anhydrous cannon mud prepared in Comparative Example 2 is 27.6%, which is less than 29.8% of Comparative Example 5; and the compressive strength test data of the anhydrous cannon mud prepared in Comparative Example 2 is 28.2MPa, which is greater than 27.3MPa of Comparative Example 5. It shows that adding carbon black alone to the raw material components can reduce the apparent porosity of the anhydrous cannon mud and improve the compressive strength.

[0108] Combined with Comparative Example 3, it can be seen that compared with Comparative Example 2, Comparative Example 3 uses modified carbon black after surface oxidation modification of carbon black. As a result, the test data of the apparent porosity of the anhydrous cannon mud prepared in Comparative Example 3 is 26.0%, which is less than 27.6% of Comparative Example 2; and the test data of the compressive strength of the anhydrous cannon mud prepared in Comparative Example 3 is 30.4MPa, which is greater than 28.2MPa of Comparative Example 2. It shows that the apparent porosity of the anhydrous cannon mud can be further reduced and the compressive strength can be improved by using carbon black as a raw material component after being made into the modified carbon black of the present invention.

[0109] By comparing Comparative Examples 1 and 2 with Comparative Examples 4 and 5, it can be seen that the addition of carbon black can offset the negative impact of the addition of calcium carbonate on the performance of the anhydrous cannon mud; but at the same time, calcium carbonate will also cause the positive effect of carbon black on the performance of the anhydrous cannon mud to decrease.

[0110] By comparing Example 1 and Comparative Example 3 with Comparative Example 4 and Comparative Example 5, it can be seen that the addition of the modified carbon black of the present invention can not only offset the negative impact of the addition of calcium carbonate on the performance of the anhydrous cannon clay; moreover, the modified carbon black and calcium carbonate can produce a synergistic effect to synergistically improve the performance of the anhydrous cannon clay, so that the performance improvement effect is better than the positive effect of the modified carbon black (alone) on the performance of the anhydrous cannon clay.

[0111] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0112] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing anhydrous taphole mud for preventing leakage, characterized in that: The steps include: S1. Put 28-32 parts of corundum, 25-30 parts of bauxite, 9-13 parts of clay, 5-8 parts of kyanite, 7-12 parts of ferrosilicon nitride, 12-17 parts of silicon carbide, 5-8 parts of calcium carbonate and 7-10 parts of modified carbon black into a dryer by weight, heat to 100-120° C., stir and dehydrate at 0.5-0.7 MPa, and obtain a dry raw material when the Engler viscosity is 9-11 and the water content is less than 0.5wt%; S2, putting the dry raw material obtained in S1 into a mixer for stirring and mixing to obtain a first mixed material; S3, adding 10-15 parts of a binder to the first mixture obtained in S2, and continuing to stir and mix to obtain a second mixture; S4, extruding the second mixed material obtained in S3 from the discharge port of the mixer to obtain leak-proof waterless taphole mud; The preparation method of the modified carbon black comprises the following steps: A1. Add 100 g of carbon black and 800-1000 mL of nitric acid solution into a beaker, react at 45-50 ° C for 3-3.5 hours, then cool to room temperature, filter, and obtain treated carbon black; A2, washing the treated carbon black obtained in A1 with deionized water until the pH value of the washing liquid is constant, thereby obtaining washed carbon black; A3. Dry the cleaned carbon black obtained in A2 to obtain modified carbon black.

2. The method for preparing the anti-leakage anhydrous taphole mud according to claim 1, characterized in that: In the A1, the mass fraction of the nitric acid solution is 62-68%.

3. The method for preparing the anti-leakage anhydrous taphole mud according to claim 1, characterized in that: In the A3, the drying temperature is 120-130° C. and the drying time is 5-6 hours.

4. The method for preparing the anti-leakage anhydrous taphole mud according to claim 1, characterized in that: In the S1, the particle size of corundum is 0.27-0.35 mm, the particle size of bauxite is 1-3 mm, the particle size of clay is 0.074-0.085 mm, the particle size of kyanite is 0.24-0.35 mm, the particle size of ferrosilicon nitride is 0.084-0.095 mm, the particle size of silicon carbide is 0.071-0.083 mm, and the particle size of calcium carbonate is 0.84-0.95 mm.

5. The method for preparing the anti-leakage anhydrous taphole mud according to claim 1, characterized in that: In S2, at 42-46°C, the speed of the stirrer is 600-650 r / min, and the stirring time is 2-4 min.

6. The method for preparing the anti-leakage anhydrous taphole mud according to claim 1, characterized in that: In S3, at 42-46° C., the rotation speed of the stirrer is 800-850 r / min, and the stirring time is 20-24 min.

7. The method for preparing the anti-leakage anhydrous taphole mud according to claim 1, characterized in that: In S4, the material temperature during extrusion is controlled to be 45-50°C.

8. The method for preparing the anti-leakage anhydrous taphole mud according to claim 1, characterized in that: The binder is tar.

Citation Information

Patent Citations

  • Special anhydrous stemming for blast furnace

    CN108101557A

  • Environmental-friendly water-free stemming for submerged arc furnace

    CN108675774A